1981
DOI: 10.1017/s0003356100040563
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interaction of ewe and lamb genotype on milk production of ewes and on growth of lambs to weaning

Abstract: Single and twin purebred Scottish Blackface lambs born to Blackface ewes, and Suffolk cross lambs born to East Friesland x Blackface ewes, were removed from their dams at birth and cross-fostered to give all combinations of breed of ewe, breed of lamb and number of lambs suckled, with no ewe rearing her own lamb.Milk production was measured on 1 day/week for 14 weeks. The effect of ewe breed was significant in all weeks, with the East Friesland cross ewes having a higher peak and a more sustained level of prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…This evidence suggests that males may be receiving more milk from their mothers. Lamb mass at weaning has proved to be a good index of the amount of milk consumed, irrespective of sex (BURRIS & BAUGUS, 1955;RICORDEAU & BOCCARD, 1961;GARDNER et al, 1964;DONEY et al, 1981;PERA BLANCO, 1985a). PERA BLANCO (1985a) found that Spanish merino ewes nursing male lambs produced more milk than ewes nursing female lambs.…”
Section: Consequentlymentioning
confidence: 99%
“…This evidence suggests that males may be receiving more milk from their mothers. Lamb mass at weaning has proved to be a good index of the amount of milk consumed, irrespective of sex (BURRIS & BAUGUS, 1955;RICORDEAU & BOCCARD, 1961;GARDNER et al, 1964;DONEY et al, 1981;PERA BLANCO, 1985a). PERA BLANCO (1985a) found that Spanish merino ewes nursing male lambs produced more milk than ewes nursing female lambs.…”
Section: Consequentlymentioning
confidence: 99%
“…These were balanced across treatments during the allocation of animals. In general in early lactation, larger lambs will obtain more milk by stimulating yield (Doney, Peart and Smith, 1981). The comparisons by Gallo and Davies (1988) of ewes rearing twins or triplets showed only small differences in milk yield at day 20 of lactation (4-1 v. 4-3 kg/day) and day 30 (3-7 v. 41 kg/day respectively).…”
Section: Number Of Foetuses Carried In Pregnancymentioning
confidence: 94%
“…Only in the final period of lactation, from 9 weeks to weaning, did lamb growth rate differ significantly between sward height treatments. This was a period when there was less difference in sward height between treatments, it is also a period when lamb growth could be expected to be affected by variation in herbage intake as milk declines (Doney et al, 1981). In general, ewes across all treatments lost live weight during this period, suggesting that milk yield was being supported by the catabolism of body tissue.…”
Section: Ewe and Lamb Performance During Lactationmentioning
confidence: 98%